Mutational Analysis of the OprM Outer Membrane Component of the MexA-MexB-OprM Multidrug Efflux System of Pseudomonas aeruginosa - Li, Xian-Zhi (American Society for Microbiology, 2001)
OprM is the outer membrane component of the MexA-MexB-OprM efflux system of Pseudomonas aeruginosa. Multiple-sequence alignment of this protein and its homologues identified several regions of high sequence conservation that were targeted for site-directed mutagenesis. Of several deletions which were stably expressed, two, spanning residues G199 to A209 and A278 to N286 of the mature protein, were unable to restore antibiotic resistance in OprM-deficient strains of P. aeruginosa. Still, mutation of several conserved residues within these regions did not adversely affect OprM function. Mutation of the highly conserved N-terminal cysteine residue, site of acylation of this presumed lipoprotein, also did not affect expression or activity of OprM. Similarly, substitution of the OprM lipoprotein signal, including consensus lipoprotein box, with the signal peptide of OprF, the major porin of this organism, failed to impact on expression or activity. Apparently, acylation is not essential for OprM function. A large deletion at the N terminus, from A12 to R98, compromised OprM expression to some extent, although the deletion derivative did retain some activity. Several deletions failed to yield an OprM protein, including one lacking an absolutely conserved LGGGW sequence near the C terminus of the protein. The pattern of permissive and nonpermissive deletions was used to test a topology model for OprM based on the recently published crystal structure of the OprM homologue, TolC (V. Koronakis, A. Sharff, E. Koronakis, B. Luisi, and C. Hughes, Nature 405:914–919, 2000). The data are consistent with OprM monomer existing as a substantially periplasmic protein with four outer membrane-spanning regions.